Analisis Praktik Corporate Social Responsibility Perusahaan Furniture di Kabupaten Jepara - Aida Nahar (Universitas Muhammadiyah Yogyakarta, Indonesia, 2012)
Corporate social responsibility (CSR) is a transparent business practices, which are based on ethical values, with particular attention to employees, communities and the environment, and designed to meet the wishes of the shareholders and the public in general. Effort to understand and analyze the practice of CSR in a company is interesting, considering the practice of CSR is not a uniform practice and its implementation is highly dependent on the unique characteristics inherent in the company. The purpose of this study is to investigate to find out the practice of Corporate Social Responsibility by furniture companies in Jepara. Data collection methods used in this study were interviews, direct observation, and analysis of company documents. Data were analyzed by triangulation and interpretation. From the research conducted it can be concluded that the comapany’s motivation in implementing CSR undertaken by the company from Jepara regency furniture is the company’s commitment and enhance the reputation of the company. While the practice of CSR that have been made furniture enterprises in Jepara regency consists of several fields, namely a). economy, including internal and external sectors. Internal sector is focused on training programs for employees. The external sector was focused on facilitating the community development patterns, community groups, and cooperatives. b). Social areas, including the provision of public facilities (infrastructure development), social welfare, education and sports. c). Environment areas, including sustainable water supply.